Model Pelayanan Kesehatan ditinjau dari Aspek Kualitas, Manajemen dan Sumber Daya Kesehatan di RSUP dr. Kariadi Semarang 2018 - Ngadiyono Ngadiyono; Endri Astuti; Istirochah Istirochah; Srie Rejeki; Yahya Renaningrum (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2019)
Current service providers must maintain quality, if customers do not want to be left behind. This includes Health Services from the Aspects of Perception of Quality, Management and Human Resources (HR) Health implemented at Dr. Hospital. Kariadi Semarang.The study was carried out using an interpretive qualitative naturalistic type / approach. With concurrent transpormative strategies, namely starategi uses a theoretical perspective to form a framework for research topics, data collection techniques and expected results from research.The results showed that the perceptual aspects of service quality were carried out in accordance with the SPO, local values, administration and regula- tion that were tailored to the patient's needs, responsive by being asked 3T and 1D (ask: conditions, complaints and facilities and prayers), and oriented to International Patient Safety Goal (IPSG) Case management (Interprofessional collaboration), limited to multidisciplinary models with authority authority in the form of Doctor in Charge of Services (DPJP) and Nurse Responsible Services (PPJP) and assisted by Associate Nurses (PA) provided interdisciplinary means and integrated notes as a model of interaction between professionals who are bound in teams. Next for the management of Human Resource management, (education, service coordination, compliance, transition management, and utilization manage-ment), it has been implemented as needed and is a comfortable place for a career.The three aspects of management's assessment, have been implemented well, only in case management using a multidisciplinary model, and have not used an international collaborative model, with limited interaction between professions in managing patients that still need to be improved.